New blue fluorescent and highly thermostable polyimide and poly(amide-imide)s containing triphenylamine units and (4-dimethylaminophenyl)-1, 3, 4-oxadiazole side groups. (January 2018) - Hamciuc, Corneliu; Hamciuc, Elena; Homocianu, Mihaela; Nicolescu, Alina; Lisa, Gabriela
Abstract: A new blue fluorescent aromatic diamine, 2-(4, 4′-diamino-4″-triphenylamine)-5-(4-dimethylaminophenyl)-1, 3, 4-oxadiazole, is synthesized in several steps. Based on this diamine four fluorescent imide-type polymers, a polyimide and three poly(amide-imide)s, are prepared by solution polycondensation reactions. The structures of the monomers and polymers are characterized by FTIR and NMR spectroscopy. The polymers show good solubility in organic solvents, and have high thermal stability, the decomposition temperature being above 380 °C, as is determined by TGA measurements. The thermal degradation mechanism of a polymer in an inert atmosphere is investigated by using the coupled TG/MS/FTIR technique. The optical properties are determined by UV-vis and fluorescence spectroscopy. The polymers exhibit strong absorption bands in the range of 357–373 nm, and blue fluorescence in solution within the range of 423–469 nm with low to moderate quantum fluorescence yields from 0.11 to 1.30% and Stokes shifts values of around 77 nm. The protonation is found to affect the spectral properties of the polymers. Graphical abstract: Highlights: A new blue fluorescent diamine having a triphenylamine group and 1, 3, 4-oxadiazole ring was synthesized. Highly thermostable aromatic polyimide and poly(amide-imide)s with blue fluorescent properties were prepared. A thermal decomposition study was performed. The fluorescence characteristics were determined in solution using different solvents. The fluorescence quenching process was studied in the presence of hydrochloric acid.